Mitigation measures for delay in dam’s project - A case study in Pakistan - Sohoo, Shujauddin; Syed Mohamad, Syed Burhanuddin Hilmi; Yunus, Riduan; Ahmed Memon, Mansoor (2024)
Construction sector is known as main sector which contributes major role in term of employment as compared to other sectors in developing countries as well as developed countries. But unfortunately, this sector is still facing many challenges which including construction delay, construction cost overrun and also construction quality standards. Pakistan is also facing these problems for the last many decades. The main purpose of this research is to find out the significant factors which contribute construction delay in dam projects of Pakistan. To achieve the objective, a deep literature review and pass research was conducted which helped to identify 48 general factors of delay in the construction sector. On basis of general factors, a questionnaire was designed and distributed among stakeholders of dam projects. The designed questionnaire was based on Likert scale from 1 to 5. Gathered data from respondents was analyzed with help of average mean value which helped to identify the 8 significant factors which causes delay in construction of dam projects of Pakistan. Another questionnaire was prepared based on the critical factors identified in this case study will be beneficial for the stakeholders to control the significant factors in construction of dam projects of Pakistan